Influence of sodium reduction and storage temperature on the growth of total microbes and Bacillus cereus in naturally contaminated hamburger patty and loaf bread - Chang, Ho-Seok (Food Sci Biotechnol, 2020)
This study aimed to investigate the influence of sodium reduction and storage temperature on the growth of total microbes and Bacillus cereus in naturally contaminated hamburger patty and loaf bread, respectively. The sodium reduction rate of hamburger patty and loaf bread was 20% and 30%, respectively, and experimental samples were kept at 4 °C, 25 °C, and 40 °C for 60 h. The microbiological analysis included the colony count of total microbes and B. cereus. The water activity (Aw), titratable acidity (TA), and pH were assessed as factors that inhibit microbial growth. In this study, Aw, TA, and pH of all samples were affected by the growth of total microbes and B. cereus during the storage period. Hence, these results suggested that sodium reduction in processed foods should be preferentially applied as a potent inhibition strategy after accurate assessment of inhibitors for different food types.